2013
DOI: 10.1068/p7607
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Visual Figure Discrimination, Verbal Abilities, and Gender

Abstract: This study investigated the relationships between verbal thinking and performance on visual figure discrimination tasks from a Vygotskian perspective in a large varied adult sample (N = 428). A test designed to assess the structure of word meanings (ie tendency to think in 'everyday' or 'scientific' concepts as distinguished by Vygotsky) together with two contour picture tasks was presented. Visual tasks were a modified version of Poppelreuter's overlapping figures and a picture depicting a meaningful scene. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This idea is consistent with the theoretical framework on conceptual thinking. For example, complex visuospatial abilities are highly related to the development of logical thinking (see Tammik and Toomela, 2013 ; Toomela et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea is consistent with the theoretical framework on conceptual thinking. For example, complex visuospatial abilities are highly related to the development of logical thinking (see Tammik and Toomela, 2013 ; Toomela et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigative interviews involve systematically gathering detailed, accurate accounts of a situation or event (Powell et al, 2005;St-Yves, 2014). It is known that children are more susceptible to suggestive questioning tactics than adults (Ceci and Friedman, 2000;Melnyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that word meaning structure is associated with visu o spatial abilities. Recent studies have indicated that there is a relationship between dominant logical thought and visuospatial abilities (Tammik and Toomela 2013;Toomela et al 2019). These findings suggest that analysis of visuospatial sensory information is semiotically mediated.…”
Section: Introductionmentioning
confidence: 95%
“…The development of logical concepts allows an individual to mentally analyse sensory information in a more abstract way (Toomela et al 2019). Prior studies have examined the relationship between dominant logical word meaning structure, discrimination, and mental rotation (Tammik and Toomela 2013;Toomela et al 2019). The findings indicate that better performance in visuospatial tasks is related to more dominant logical thought.…”
Section: Introductionmentioning
confidence: 99%